2021
DOI: 10.3389/fphy.2020.567300
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning of GPU–Accelerated Monte Carlo Code FRED for Clinical Applications in Proton Therapy

Abstract: We present commissioning and validation of Fred, a graphical processing unit (GPU)–accelerated Monte Carlo code, for two proton beam therapy facilities of different beam line design: CCB (Krakow, IBA) and EMORY (Atlanta, Varian). We followed clinical acceptance tests required to approve the certified treatment planning system for clinical use. We implemented an automated and efficient procedure to build a parameter library characterizing the clinical proton pencil beam. Beam energy, energy spread, lateral prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…This underestimation could in part be explained through the fact that the current approach for sampling the initial particles neglects secondary d, t, 3 He and 4 He particles produced in the beamline. Our predictions are in line with other fast MC engines available in literature, for example [73], using FRED have found relative differences of up to about 3% for 200 MeV protons in water.…”
Section: Field Strength [T]supporting
confidence: 92%
See 2 more Smart Citations
“…This underestimation could in part be explained through the fact that the current approach for sampling the initial particles neglects secondary d, t, 3 He and 4 He particles produced in the beamline. Our predictions are in line with other fast MC engines available in literature, for example [73], using FRED have found relative differences of up to about 3% for 200 MeV protons in water.…”
Section: Field Strength [T]supporting
confidence: 92%
“…The 3D gamma pass rate was calculated to be 99.8% showing that the implemented models and approximations for electromagnetic and nuclear interactions approximate the underlying physics well, also in a clinical setting. Computed 3D gamma pass rates were in line with those obtained by other fast MC engines [28,33,73].…”
Section: Field Strength [T]supporting
confidence: 80%
See 1 more Smart Citation
“…Images were captured using the Fiji open-source software [ 23 ]. Next, in the context of signal processing, images were corrected and analyzed in the Python environment, importing, among others, the functionalities FRED tools module [ 24 , 25 , 26 ]. Pixel intensities depend on several parameters and may be reflected in the camera setup parameters, image distortions or powder distribution inside the silicone matrix.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Riberio et al reported on the development and application of a plan evaluation tool, 4D robust evaluation method (4DREM), which considers both setup errors as well as respiratory motion and the interplay effects (112), while Korevaar et al developed a scenariobased plan evaluation method which allows for comparison between photon and proton plans (113). In another hand, fast 4D dose calculation with GPU-accelerated dose-engines enable potential clinical use and can be integrated into the optimization process (114)(115)(116). Another consideration for 4D dose calculation is that the temporal resolution used can impact the calculated final accumulated dose distribution, a recent simulation study found that the use of finer temporal resolutions for 4D dose calculations can help to reduce the over-estimation of interplay effects for hypo-fractionated treatments (19).…”
Section: Plan Evaluationmentioning
confidence: 99%